2011
DOI: 10.1093/rheumatology/ker258
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary dysfunction, smoking, socioeconomic status and the risk of developing rheumatoid arthritis

Abstract: Pulmonary dysfunction did not predict RA, but smoking and low socio-economic status were independent risk factors for RA. Other effects of smoking may be important for RA susceptibility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
52
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(59 citation statements)
references
References 36 publications
5
52
1
1
Order By: Relevance
“…Directly relevant to this, a nested case control analysis from a population-based study carried out in Malmö, Sweden found that blue collar occupations manifested an increased risk of rheumatoid arthritis (Odds Ratio 1.59; 95% CI 1.12-2.26), taking into current smoking and lung function defined COPD (which would reflect a chronic smoking burden, although this also could have over-adjusted for the effects of dusty work which can also cause COPD). 19 The pattern of risk that we observed also raises intriguing additional questions in relation to previous studies of silica and rheumatoid arthritis characterized by serologic status. The populationbased case-referent investigation of rheumatoid arthritis in Sweden (the Epidemiological Investigation of Rheumatoid Arthritis study) observed a strong association between rheumatoid arthritis and selfreported occupational exposure to silica, but the increased risk was restricted those with seropositive disease; silica was not a risk factor for seronegative rheumatoid arthritis.…”
mentioning
confidence: 61%
See 1 more Smart Citation
“…Directly relevant to this, a nested case control analysis from a population-based study carried out in Malmö, Sweden found that blue collar occupations manifested an increased risk of rheumatoid arthritis (Odds Ratio 1.59; 95% CI 1.12-2.26), taking into current smoking and lung function defined COPD (which would reflect a chronic smoking burden, although this also could have over-adjusted for the effects of dusty work which can also cause COPD). 19 The pattern of risk that we observed also raises intriguing additional questions in relation to previous studies of silica and rheumatoid arthritis characterized by serologic status. The populationbased case-referent investigation of rheumatoid arthritis in Sweden (the Epidemiological Investigation of Rheumatoid Arthritis study) observed a strong association between rheumatoid arthritis and selfreported occupational exposure to silica, but the increased risk was restricted those with seropositive disease; silica was not a risk factor for seronegative rheumatoid arthritis.…”
mentioning
confidence: 61%
“…10,11 In Scandinavia in particular, population-based case referent studies and linkage of census-defined occupation and hospitalization records have provided valuable insights into the potential relationships among occupational exposures, including to silica containing and other mineral dusts, and selected rheumatologic conditions, especially rheumatoid arthritis. [12][13][14][15][16][17][18][19] Sample size considerations, however, generally preclude occupationally-defined cohort investigations of rheumatologic diseases, especially conditions other than rheumatoid arthritis. A study of granite workers in Finland with more than 10,000 person years of observation that found a 70% increase risk of rheumatoid arthritis is a rare example of a cohort-based approach.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous survey,17 we identified individuals who developed RA after inclusion in this cohort and up to 31 December 2004, by linking the MPMP register to a community-based RA register,18 19 the local outpatient clinic administrative register for Malmö University Hospital, the National Hospital Discharge Register and the National Cause of Death Register 17. The community-based RA register has been shown to include more than 90% of patients in the catchment area 19.…”
Section: Methodsmentioning
confidence: 99%
“…Data on socioeconomic status were derived from self-reported job titles in the Swedish national censuses, as previously described 17. Briefly, occupations were coded and converted into standardised social class categories, and subjects were classified as ‘blue-collar workers’ (manual workers, both skilled and unskilled), ‘white-collar workers’ (non-manual employees and self-employed professionals) and ‘others’.…”
Section: Methodsmentioning
confidence: 99%
“…[34] Sigara, RA geliflimi için bir risk faktörüdür. [35] ‹çilen paket/y›l miktar› artt›kça RA geliflme riski de o oranda art›fl göste-rir. [36] Sigara ayn› zamanda ‹AH geliflme riskini de art›r-maktad›r.…”
Section: Risk Faktörleriunclassified